Knowledge and Attitude of Mothers about Children Immunization and Barriers to Adherence the Program, in Erbil City - Suham Mir Hamad Abdullah; Ibrahim Hasan Mustafa (Hawler Medical University, 2022)
Background and objective: Immunization programs are one of the most important methods to prevent infections and sickness among children. We can overcome many obstacles if mothers have the necessary knowledge and attitude regarding vaccines. The study aims to assess mothers' knowledge, attitudes, and barriers related to immunization programs and associations related to socio-demographic characteristics. Methods: A cross-sectional study design was carried out in Erbil city across six primary health care centers (Hawkari, Azadi, Runaki, Shadi, Mala Afandi, and Nazdar Bamarni) during the period of January 5, 2021, to April 8, 2021. Non-probability convenience sampling methods were used. The sample consisted of 410 mothers ages 18 and older. A questionnaire with four parts (socio-demographic characteristics, knowledge, attitude, and barriers to adherence immunization programs) was used to collect data. Statistical package for Social Science (version 23) was used for data analysis. Chi-square and Fisher exact tests were used to determine the association between socio-demographic characteristics and knowledge and attitudes. Frequency and percentage were used to identify barriers. Results: The study findings showed a statistically significant association between the knowledge of mothers and their age, educational level, occupation, and socioeconomic status. Mothers have a high attitude regarding immunizations. The majority (69.3%) of mothers have not had any missed opportunities for not given immunizations. The most common reasons for not giving immunizations were mothers being busy and child sickness at the time of immunizations. Conclusions: There was statistically significant association between mother's knowledge and age, education, occupations, and socioeconomic status. A high level of attitude was recorded among mothers regarding immunizations. Mothers reported being busy on the day of the immunizations and child sickness as the most common barriers to receiving immunizations.